Modeling and Multi-Objective Optimization of Thermophysical Parameters of Hybrid Nanodiamond–Ni-Based Nanofluids via Response Surface Methodology - Alsaady, Mustafa (Frontiers in Mechanical Engineering, 2021)
The present study comprises the modeling and optimization of thermal and viscous properties of nanodiamond-nickel (Ni) particle-based nanofluid in ethylene glycol. The temperature and nanoparticle weight percent are selected as process variables, which are considered crucial for the operational condition of the application and the economic factor. The impact of these process variables was investigated on thermal conductivity and viscosity simultaneously using Response Surface Methodology (RSM). The models for thermal conductivity and viscosity were developed and validated using experimentally measured property data. The validated model was further used for the prediction. A detailed multi-objective optimization study was conducted to maximize thermal conductivity and minimize viscosity. The optimum results suggested that the maximum values for thermal conductivity and viscosity of nanofluids were estimated as 0.282 Wm/°C and 5.867 mPa.s, respectively. The optimum values for input parameters such as temperature and nanodiamond-nickel (Ni) concentration were calculated as 60oC and 2.998 wt.%, respectively. The coefficient of determination R2 for the developed model showed 0.9971 and 0.9975 for thermal conductivity and viscosity, respectively.